Pengembangan E-LKPD Berdiferensiasi Berbasis Proyek Sebagai Inovasi Pembelajaran IPAS Kreatif Kelas V SD/MI - Dewi Larasati, Nurfadila; Sri Latifah; Muhammad Muchsin Afriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the need for teaching materials that can accommodate students' diverse abilities and interests, as well as encourage active engagement in the learning process. The main objectives of this study are: (1) to develop a valid project-based differentiated E-worksheet (E-LKPD) as an innovative and creative IPAS learning tool for fifth-grade elementary students, and (2) to determine the responses of educators and students toward the project-based differentiated E-LKPD as an innovative and creative IPAS learning tool for fifth-grade elementary students. This study employs a research and development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Based on the validity tests conducted by three experts, the project-based differentiated E-LKPD received an average validation score of 92.95%, categorized as highly valid. In terms of practicality, the overall percentage obtained was 91,94%, categorized as highly practical. These results indicate that the E-LKPD is engaging and applicable in elementary school learning.